Strategic Inattention in Product Search - Svenja Hippel; Adrian Hillenbrand (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
Online platforms provide search tools that help consumers to get better-fitting product offers. But this technology makes consumer search behavior also easily traceable and allows for real-time price discrimination. Consumers face a trade-off: Search intensely and receive a better fit at a potentially higher price or restrict search behavior – be strategically inattentive – and receive a worse fit, but maybe a better deal. We study the resulting strategic buyer-seller interaction theoretically as well as experimentally. Our experimental results show that it is the sellers and not the buyers who profit from these search tools.
Keywords: D11; D42; D82; D83; L11; 330; strategic inattention; price discrimination; information transmission; consumer choice; experiment